2010
DOI: 10.3892/ol_00000073
|View full text |Cite
|
Sign up to set email alerts
|

Expression of matrix metalloproteinase-10 in non-metastatic prostate cancer: Correlation with an imbalance in cell proliferation and apoptosis

Abstract: Abstract. Matrix metalloproteinases (MMPs) are associated with cell invasion under various physiological and pathological conditions. Among MMPs, MMP-10 is reported to correlate with a high pT stage and progression in a variety of cancer types. However, the clinical and pathological significance of MMP-10 in human prostate cancer tissues remains unclear. This study aimed to clarify the role of MMP-10 in non-metastatic prostate cancer. Sixty-three specimens were obtained by radical prostatectomy. MMP-10 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…In particular, compared to other MMPs, MMP-10 has a relatively broad substrate specificity and has been demonstrated to degrade a variety of matrix and non-matrix components (Bodey et al, 2001). Besides mainly participating in tumor invasion and metastasis, MMP-10 were even found to inhibit cancer cell apoptosis (Maruta et al, 2010). Therefore, proapoptotic activity of chrysin may also correlate with the inhibition of MMP-10.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, compared to other MMPs, MMP-10 has a relatively broad substrate specificity and has been demonstrated to degrade a variety of matrix and non-matrix components (Bodey et al, 2001). Besides mainly participating in tumor invasion and metastasis, MMP-10 were even found to inhibit cancer cell apoptosis (Maruta et al, 2010). Therefore, proapoptotic activity of chrysin may also correlate with the inhibition of MMP-10.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they speculated that MMP-10 modulates tumor growth via the regulation of the balance of cell proliferation and apoptosis. 88 Singh et al showed that interactions between chemokine receptor CXCR5 and chemokine CXCL13 had an influence to the expression of MPP-10 in PCa. In cell lines of PCa cultured with or without CXCL13, changes in expression of MMP-10 was observed.…”
Section: Mmp-10 In Carcinogenesis Of Cancersmentioning
confidence: 99%
“…2F), indicating a role for LIMK activity in androgen-induced motility. Expression of the matrix metalloproteinases MMP-10 (35) and MMP-1 (36), which had previously been implicated in prostate tumor growth, were not affected by DHT or LIMKi treatment (Supplementary Fig S1D). Interestingly, when LNCaP cells were treated with 10 μM LIMKi we readily observed reduced LNCaP cell numbers.…”
Section: Resultsmentioning
confidence: 84%